PENGARUH VARIASI DIAMETER THROTTLE BODY DAN PUTARAN MESIN TERHADAP DAYA DAN KONSUMSI BAHAN BAKAR SPESIFIK PADA MESIN BENSIN BERKAPASITAS 149 CC: THE EFFECT OF VARIATION IN THROTTLE BODY DIAMETER AND ENGINE SPEED ON POWER AND SPECIFIC FUEL CONSUMPTION IN A 149 CC GASOLINE ENGINE - Indra Wahyu Prasetyo (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
The purpose of this study is to determine whether there is a significant effect by replacing the throttle body diameter variation on power and specific fuel consumption in a 149cc gasoline engine. This research uses the experimental design method. The results obtained the highest power data value of 10.2 HP achieved at 3500 rpm when using a 26mm throttle body, the highest power data value of 10.3 HP achieved at 5000 rpm when using a 28mm throttle body, the highest power data value of 11 HP achieved at 3500 rpm when using a 30mm throttle body. For the largest specific fuel consumption data value when using a 26mm throttle body of 0.0574785 kg/hp.h achieved at 5500 rpm, the largest specific fuel consumption data when using a 28mm throttle body of 0.05806907 kg/hp.h achieved at 5500 rpm, and the largest specific fuel consumption data when using a 30mm throttle body of 0.06013069 kg/hp.h achieved at 5500 rpm.